2010
DOI: 10.1063/1.3290957
|View full text |Cite
|
Sign up to set email alerts
|

Quantum gate operations using midinfrared binary shaped pulses on the rovibrational states of carbon monoxide

Abstract: Frequency domain shaped binary laser pulses were optimized to perform 2 qubit quantum gate operations in (12)C(16)O. The qubit rovibrational state representation was chosen so that all gate operations consisted of one-photon transitions. The amplitude and phase varied binary pulses were determined using a genetic algorithm optimization routine. Binary pulses have two possible amplitudes, 0 or 1, and two phases, 0 or pi, for each frequency component of the pulse. Binary pulses are the simplest to shape experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…[15][16][17][18][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The Deutsch-Jozsa algorithm is one of the elementary algorithms in quantum computation. This algorithm was simulated theoretically using vibrational states of acetylene 18 and electronic excited states of iodine.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The Deutsch-Jozsa algorithm is one of the elementary algorithms in quantum computation. This algorithm was simulated theoretically using vibrational states of acetylene 18 and electronic excited states of iodine.…”
Section: Introductionmentioning
confidence: 99%
“…SO 2 is one typical normal mode molecule, in which the coupling between different vibrational modes is strong. The strong coupling is critical for the quantum parallelism computation, for example, the strong coupling was found to play an important role in the CNOT (Controlled‐NOT) quantum logic gate . However, some investigations also found that the coupling could induce the decrease of fidelity of quantum gates, as the coupling between the qubit system and the remaining vibrational mode is one important resource of decoherence .…”
Section: Introductionmentioning
confidence: 99%
“…11 The many theoretical contributions include, (i) studying molecular systems: modes of acetylene, 6,12,13 ammonia, 14,15 and thiophosgene, 16 vibrational/ro-vibrational excitaa) Electronic mail: alex.brown@ualberta.ca. tions within diatomics, [17][18][19][20][21][22][23][24][25] and of dipole-dipole coupled diatomics, 26 and (ii) investigating experimental issues. 10,27,28 Many of the theoretical studies were based on iterative optimal control theory 29 (OCT) and the resulting pulses were inaccessible to present experiments, e.g., shaped in both the mid-IR and microwave frequency regimes.…”
Section: Introductionmentioning
confidence: 99%